Navigating the energy trilemma during geopolitical and environmental crises - Richard S. J. Tol (Asian Development Bank Institute (ADBI), 2023)
There are many indicators of energy security. Few measure what really matters-an affordable and reliable energy supply-and the trade-offs between the affordability and reliability. Reliability is physical, affordability is economic. The latest Russian invasion of Ukraine highlights some of the problems with energy security, from long-term contracts being broken to supposedly secure supplies being diverted to retired power plants being recommissioned to spillovers to other markets. Energy security requires government intervention. Policies on energy access and poverty should shift from price support, widespread in Asia, to income support. The transition to carbon-free energy poses new challenges for energy security, from a shift in dependence from some resources (coal, oil, gas) to others (rare earths, wind, sunshine) to substantial redundancies in the energy capital stock to undercapitalized energy companies, while regulatory uncertainty deters investment. Renewables improve energy security in one dimension, but worsen it in others, particularly due to long spells of little wind. Security problems with rare earths and borrowed capital are less pronounced. The potential for asset stranding by climate policy is particularly large in Asia.
Keywords: Q34; Q37; Q48; Q5; 330; affordability; reliability; violent conflict; climate policy